Flawless - Shepard, Sara 1977- (New York HarperTempest, 2007)
After their friend who has been missing for more than three years turns up dead, four former best friends continue to receive frightening messages from someone who knows damaging secrets about them
1
Keywords: Conduct of life -- Fiction; Friendship -- Fiction; High schools -- Fiction; Secrets -- Fiction; Detective and mystery fiction